Preparation method of ultrathin copper foil for packaging carrier plate and method for preparing copper-clad plate by using ultrathin copper foil
Through the easy peeling of the carrier substrate and the modified liquid treatment method, ultra-thin copper foil is deposited, and through the combination of hot pressing technology and semi-cured sheet, the problems of easy curling and high cost of ultra-thin copper foil are solved, and environmentally friendly copper clad plate is realized Production and low cost preparation.
Patent Information
- Application Number
- CN202411308756.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-17
AI Technical Summary
Ultra-thin copper foil is prone to curling and wrinkles during production and application, resulting in high preparation and transportation costs. The traditional method uses highly toxic heavy metal cadmium (IV) salt, which affects environmental friendliness.
Using the easy-to-peel carrier substrate and modification liquid treatment method, the conductive layer and organic coating are prepared by soaking ethanol or acetone and vapor deposition, ultra-thin copper foil is deposited, and the thermal pressing technology is used to combine it with the semi-cured sheet, and finally the carrier is peeled off. The substrate is to form a copper clad plate.
The cost of preparing ultra-thin copper foil is reduced, the stability of ultra-thin copper foil is ensured in storage and transportation, the use of highly toxic heavy metals is avoided, and environmentally friendly copper clad production is achieved.
Smart Images

Figure CN119145011A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminate processing, and in particular to a method for preparing an ultra-thin copper foil for a packaging carrier and a method for preparing a copper clad laminate using the ultra-thin copper foil. Background Art
[0002] During the production and manufacturing process of ultra-thin copper foil, due to its light and thin characteristics, ultra-thin copper foil is very prone to curling and wrinkling during the production and application process, which increases the difficulty of back-end application. Therefore, at present, ultra-thin copper foil is basically produced in the form of peelable copper foil with carrier, that is, using thicker copper foil such as 18 microns or 35 microns as a carrier, accurately constructing a separation layer (a special interface layer formed by chemical treatment or physical plating) on its surface, and then depositing a layer of ultra-thin copper foil with a thickness of only 1~5 μ on this interface layer. In the subsequent production process of copper clad laminates or package carriers, the composite material with ultra-thin copper foil on this side is flatly laminated with the prepreg, and the two are tightly combined by hot pressing. Subsequently, the original copper foil carrier is easily peeled off by mechanical or chemical methods, leaving only the ultra-thin copper foil layer attached to the prepreg as the basis for subsequent circuit production. The use of carrier copper foil, the preparation of the separation layer, and the precise combination of the two significantly increase the preparation cost and transportation cost of ultra-thin copper foil. Therefore, while promoting the development of packaging substrate technology, how to optimize the preparation process of ultra-thin copper foil and reduce costs has become an urgent problem to be solved. Summary of the invention
[0003] The present invention provides a method for preparing an ultra-thin copper foil for a packaging carrier and a method for preparing a copper-clad laminate using the ultra-thin copper foil, so as to solve the above-mentioned deficiencies of the prior art, optimize the preparation process of the ultra-thin copper foil and reduce the cost.
[0004] In order to achieve the purpose of the present invention, the following technologies are proposed: A method for preparing an ultra-thin copper foil for a packaging carrier comprises the following steps: Step 1, soaking the carrier substrate with ethanol or acetone; Step 2, the carrier substrate obtained in step 1 is immersed in the modification liquid A; Step 3, preparing a conductive layer on the surface of the carrier substrate obtained in step 2 by vapor deposition; Step 4, immersing the carrier substrate obtained in step 3 in a modification solution B, so that an organic coating with a thickness of 700 to 10000 Å is prepared on the surface of the conductive layer; Step 5, placing the carrier substrate treated in step 4 in a copper electroplating solution and preparing an ultra-thin copper foil on the organic coating by electrodeposition; Current density is 1~20 A / dm 2 , the electrolyte temperature is 40~75℃, and the electroplating time is 10~80s.
[0005] Furthermore, in step 1, the immersion time of the carrier substrate is 10-15 minutes, and the immersion temperature is 20-40°C.
[0006] Further, the carrier substrate material is one of polybenzimidazoles, sulfonated polyimides, sulfonated polyaryletherketones, sulfonated polyarylethers, sulfonated polyesters, and sulfonated polyester-blended polyolefins; The thickness of the carrier substrate is 6~18μm.
[0007] Furthermore, in step 2, the soaking temperature is 20-80° C., and the soaking time is 30-150 s.
[0008] Furthermore, the solute of the modified solution A in step 2 is one or two of the thiazole / thiadiazole / imidazole / pyridine / pyrimidine / triazole / piperazine small molecule (Mw≤200 g / mol) compounds containing a monoamino / thiol / hydroxyl / carboxyl / sulfonic acid group; The total solute concentration of modified solution A is 1 to 5 g / L; The solvent of the modified liquid A is a mixture of deionized water and an organic solvent; The boiling point of the organic solvent is bp≤150℃ and the toxicity is LD50≥2900 mg / kg; The volume ratio of deionized water to organic solvent in modified liquid A is 1:(0.25~4).
[0009] Further, the thickness of the conductive layer in step 3 is 800 to 2500 Å; The conductive layer is made of an iron-based alloy layer, a cobalt-based alloy layer, a titanium-based alloy or conductive carbon.
[0010] Furthermore, the soaking temperature in step 4 is 20-30° C., and the soaking time is 30-70 seconds.
[0011] Furthermore, the solute of the modified solution B in step 4 is one or two of triazole / thiazole / thiadiazole / imidazole small molecule (Mw≤200 g / mol) compounds; The total solute concentration of modified solution B is 1 to 5 g / L; The solvent of the modified liquid B is a mixture of deionized water and an organic solvent; The volume ratio of water to organic solvent in the solvent of modified liquid B is 1:(0.05~2); The boiling point of organic solvents is bp≤150℃ and the toxicity is LD50≥2900 mg / kg.
[0012] Further, the copper salt concentration in the copper electroplating solution in step 5 is 100 to 300 g / L; Sulfuric acid concentration is 50-120 g / L; The Cl / Br ion concentration is 20-300 mg / L; The concentration of sodium polydisulfide dipropane sulfonate is 0.2~1.2 g / L; Hydroxymethylcellulose concentration ≤ 100 mg / L; Gelatin concentration ≤80 mg / L; Polyethyleneimine concentration ≤ 1000 mg / L; The molecular weight of polyethyleneimine is Mw≤10 kDa.
[0013] A method for preparing a copper clad laminate, comprising preparing an ultra-thin copper foil by a method for preparing an ultra-thin copper foil for a packaging carrier, and laminating the ultra-thin copper foil on a prepreg by thermal lamination; During pressing, the temperature is 30~320℃; Time is 2~6 hours; Pressure is 2~4.5 MPa; The thickness of the prepreg is 1~30mm; The prepreg is one of epoxy resin, phenolic resin, polyester and polytetrafluoroethylene; During lamination, one side of the carrier substrate with ultra-thin copper foil is attached to the prepreg, and then lamination is performed by heat pressing. After lamination, the carrier substrate, the conductive layer and the organic coating are peeled off to form a copper clad laminate.
[0014] The advantages of the above technical solution are: (1) Compared with the traditional carrier copper foil, the easy-to-peel carrier substrate used in the present invention has lower preparation cost.
[0015] (2) The peeling layer in the easily peelable carrier substrate is prepared by physical-chemical adsorption. The peeling layer and the ultra-thin copper foil have moderate bonding force, which can ensure that the ultra-thin copper foil of the carrier composite film does not wrinkle or fall off during storage and transportation.
[0016] (3) After the ultra-thin copper foil for the packaging carrier is pressed together with the prepreg, it can be completely and stably separated from the easily peelable carrier substrate.
[0017] (4) Compared with the traditional peelable carrier copper foil, the ultra-thin copper foil for packaging carrier provided by the present invention does not involve the use of highly toxic heavy metal cadmium (IV) salts in the preparation and production process, and is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0019] Figure 1The structure diagram of the ultra-thin copper foil for the packaging substrate is shown.
[0020] Figure 2 The figure shows the structure of the copper clad laminate when it is pressed together.
[0021] Figure 3 The figure shows the structure of the copper clad laminate after lamination. DETAILED DESCRIPTION
[0022] like Figure 1 As shown, the structure of the ultra-thin copper foil for packaging carrier is shown, which comprises ultra-thin copper foil 1, organic coating 2, conductive layer 3 and carrier substrate 4 from top to bottom, wherein the organic coating 2 and conductive layer 3 are peeling layers, so that the ultra-thin copper foil 1 can be peeled off from the organic coating 2. The organic coating 2, conductive layer 3 and carrier substrate 4 are easy-to-peel layers, and since the organic coating 2 and ultra-thin copper foil 1 are easy to peel off, the latter formed is an easy-to-peel layer, and in addition, the conductive layer 3 is also easy to peel off from the carrier substrate 4, so that the carrier substrate 4 can be reused by this method.
[0023] Combination Figure 2 and Figure 3 As shown, it is a schematic diagram of the copper clad laminate during the lamination and stripping process. During the lamination process, the side of the ultra-thin copper foil 1 of the structure of the above-mentioned packaging carrier is made to face the prepreg 5, and then the ultra-thin copper foil 1 is hot-pressed on the prepreg 5 by lamination. This method can avoid damage to the ultra-thin copper foil 1 during the lamination process and ensure the lamination effect. And after lamination, it is also convenient to expose the ultra-thin copper foil 1, that is, to strip off the organic coating 2, the conductive layer 3 and the carrier substrate 4.
[0024] Example 1 Step 1: Using a sulfonated polyarylether membrane with a thickness of 14 μm as a carrier substrate, soaking it in ethanol to remove surface stains, wherein the sulfonated polyarylether membrane soaking temperature is 30°C and the soaking time is 10 min.
[0025] Step 2: The sulfonated polyarylether membrane treated in step 1 is immersed in modification solution A at a temperature of 40°C for 60 seconds. The modification solution A is composed of 2-mercaptothiazole and a deionized water-ethanol mixed solvent (the content of ethanol in water is 30 wt%), and the concentration of 2-mercaptothiazole in the modification solution A is 2.5 g / L.
[0026] Step 3: Depositing a conductive carbon layer on the surface of the carrier substrate treated in step 2 by vapor deposition, wherein the thickness of the conductive carbon layer is 2000 Å.
[0027] Step 4, the carrier substrate treated in step 3 is immersed in modification solution B, the immersion temperature is 30 ° C, and the immersion time is 60 s. Modification solution B is composed of benzotriazole and deionized water-isopropanol mixed solvent (isopropanol content in water is 10wt%); the concentration of benzotriazole in modification solution A is 2 g / L, and the thickness of the prepared organic coating is 800 Å.
[0028] Step 5, prepare a copper electroplating solution. The copper electroplating solution consists of the following components: Copper sulfate pentahydrate 200 g / L; Sulfuric acid 75g / L; Cl ion 70 mg / L; Sodium polydisulfide dipropane sulfonate is 300 mg / L; Polyethylenimine (Mw = 0.2 kDa) 600 mg / L; Hydroxymethylcellulose: 20 mg / L; Gelatin is 20 mg / L.
[0029] The carrier substrate treated in step 4 is used as the cathode and immersed in a 60 ℃ copper electroplating solution for segmented electroplating. DC electroplating is first performed with a current density of 20 A / dm 2 , electroplating time 20 s, then square wave / triangle wave pulse electroplating, current density range 40 A / dm 2 , the pulse on time range is 100 ms, and the pulse off time range is 20-1500 ms. After the electroplating is completed, take it out and rinse it with deionized water and vacuum dry it.
[0030] Step 6, according to the required thickness and shape of the final copper clad laminate, the ultra-thin copper foil obtained in step 5 is hot-pressed with a FR4 epoxy resin substrate with a thickness of 10 mm, and cooled to obtain the required copper clad laminate, with a hot-pressing temperature of 220°C, a hot-pressing time of 2.5 h, and a hot-pressing pressure of 4 MPa.
[0031] Example 2 Step 1: Using a sulfonated polyarylether membrane with a thickness of 14 μm as a carrier substrate, soaking it in ethanol to remove surface stains, wherein the sulfonated polyarylether membrane is soaked at a temperature of 30° C. and for a time of 10 min.
[0032] Step 2: The sulfonated polyarylether membrane treated in step 1 is immersed in modification solution A at a temperature of 40°C for 60 seconds. In step 2), the modification solution A is composed of 4-pyridinecarboxylic acid and a deionized water-isopropanol mixed solvent (the content of isopropanol in water is 25 wt%), and the concentration of 4-pyridinecarboxylic acid in the modification solution A is 8 g / L.
[0033] Step 3: Deposit a layer of titanium-iridium alloy on the surface of the carrier substrate treated in step 2 by vapor deposition, and the thickness of the conductive layer is 1000 Å.
[0034] Step 4, the carrier substrate treated in step 3 is immersed in modification solution B, the immersion temperature is 30 ° C, and the immersion time is 60 s. Modification solution B is composed of benzotriazole and deionized water-isopropanol mixed solvent (isopropanol content in water is 10wt%); the concentration of benzotriazole in modification solution A is 2 g / L, and the thickness of the prepared organic coating is 800 Å.
[0035] Step 5, prepare a copper electroplating solution. The copper electroplating solution consists of the following components: Copper sulfate pentahydrate 200 g / L; Sulfuric acid 75g / L; Cl ion 70 mg / L; Sodium polydisulfide dipropane sulfonate is 300 mg / L; Polyethylenimine (Mw = 0.2 kDa) 600 mg / L; Hydroxymethylcellulose: 20 mg / L; Gelatin is 20 mg / L.
[0036] The carrier substrate treated in step 4 is used as the cathode and immersed in a 60 ℃ copper electroplating solution for segmented electroplating. DC electroplating is first performed with a current density of 20 A / dm 2 , electroplating time 20 s, then square wave / triangle wave pulse electroplating, current density range 40 A / dm 2 , the pulse on time range is 100 ms, and the pulse off time range is 20-1500 ms. After the electroplating is completed, take it out and rinse it with deionized water and vacuum dry it.
[0037] Step 6, according to the required thickness and shape of the final copper clad laminate, the ultra-thin copper foil obtained in step 5 is hot-pressed with a FR4 epoxy resin substrate with a thickness of 10 mm, and cooled to obtain the required copper clad laminate, with a hot-pressing temperature of 220°C, a hot-pressing time of 2.5 h, and a hot-pressing pressure of 4 MPa.
[0038] Example 3 Step 1: Using a sulfonated polyarylether membrane with a thickness of 14 μm as a carrier substrate, soaking it in ethanol to remove surface stains, wherein the sulfonated polyarylether membrane is soaked at a temperature of 30° C. and for a time of 10 min.
[0039] Step 2: The sulfonated polyarylether membrane treated in step 1 is immersed in modification solution A at a temperature of 40°C for 60 seconds. In step 2), modification solution A is composed of 2-amino-1,3,4-thiadiazole and a deionized water-isopropanol mixed solvent (the content of isopropanol in water is 25 wt%), and the concentration of 2-amino-1,3,4-thiadiazole in modification solution A is 6 g / L.
[0040] Step 3: Deposit a layer of titanium-iridium alloy on the surface of the carrier substrate treated in step 2 by vapor deposition, and the thickness of the conductive layer is 1000 Å.
[0041] Step 4, the carrier substrate treated in step 3 is immersed in modification solution B, the immersion temperature is 30 ° C, and the immersion time is 60 s. Modification solution B is composed of benzotriazole and deionized water-isopropanol mixed solvent (isopropanol content in water is 10wt%); the concentration of benzotriazole in modification solution A is 2 g / L, and the thickness of the prepared organic coating is 800 Å.
[0042] Step 5, prepare a copper electroplating solution. The copper electroplating solution consists of the following components: Copper sulfate pentahydrate 200 g / L; Sulfuric acid 75g / L; Cl ion 70 mg / L; Sodium polydisulfide dipropane sulfonate is 300 mg / L; Polyethylenimine (Mw = 0.2 kDa) 600 mg / L; Hydroxymethylcellulose: 20 mg / L; Gelatin is 20 mg / L.
[0043] The carrier substrate treated in step 4 is used as the cathode and immersed in a 60 ℃ copper electroplating solution for segmented electroplating. DC electroplating is first performed with a current density of 20 A / dm 2 , electroplating time 20 s, then square wave / triangle wave pulse electroplating, current density range 40 A / dm 2 , the pulse on time range is 100 ms, and the pulse off time range is 20-1500 ms. After the electroplating is completed, take it out and rinse it with deionized water and vacuum dry it.
[0044] Step 6, according to the required thickness and shape of the final copper clad laminate, the ultra-thin copper foil obtained in step 5 is hot-pressed with a FR4 epoxy resin substrate with a thickness of 10 mm, and cooled to obtain the required copper clad laminate, with a hot-pressing temperature of 220°C, a hot-pressing time of 2.5 h, and a hot-pressing pressure of 4 MPa.
[0045] Table 1 Performance test results Note: The peel strength in the table is tested according to the IPC-TM-650 test standard.
[0046] According to the results in Table 1, the ultra-thin copper foil obtained based on Examples 1 to 3 has good anti-oxidation properties and can be completely peeled off from the carrier substrate during the copper clad laminate lamination process. After lamination, there is good bonding strength between the copper foil and the prepreg.
[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing ultra-thin copper foil for packaging substrate, It is characterized in that Includes steps: Step 1, soaking the carrier substrate (4) in ethanol or acetone; Step 2, the carrier substrate (4) obtained in step 1 is immersed in a modification liquid A; Step 3, preparing a conductive layer (3) on the surface of the carrier substrate (4) obtained in step 2 by vapor deposition; Step 4, immersing the carrier substrate (4) obtained in step 3 in a modification solution B, so that an organic coating (2) with a thickness of 700 to 10000 Å is prepared on the surface of the conductive layer (3); Step 5, placing the carrier substrate (4) treated in step 4 in a copper electroplating solution and preparing an ultra-thin copper foil (1) on the organic coating (2) by electrodeposition; Current density is 1~20 A / dm 2 , the electrolyte temperature is 40~75℃, and the electroplating time is 10~80s.
2. The method for preparing the ultra-thin copper foil for packaging substrate according to claim 1, It is characterized in that In step 1, the carrier substrate (4) is immersed for 10 to 15 minutes at a temperature of 20 to 40°C.
3. The method for preparing the ultra-thin copper foil for packaging substrate according to claim 1, It is characterized in that The material of the carrier substrate (4) is one of polybenzimidazole, sulfonated polyimide, sulfonated polyaryletherketone, sulfonated polyarylether, sulfonated polyester and sulfonated polyester blended polyolefin; The thickness of the carrier substrate (4) is 6 to 18 μm.
4. The method for preparing the ultra-thin copper foil for packaging substrate according to claim 1, It is characterized in that In step 2, the soaking temperature is 20-80° C., and the soaking time is 30-150 seconds.
5. The method for preparing the ultra-thin copper foil for packaging substrate according to claim 1, It is characterized in that The solute of the modified solution A in step 2 is one or two of the small molecule (Mw≤200 g / mol) compounds of thiazole / thiadiazole / imidazole / pyridine / pyrimidine / triazole / piperazine containing monoamino / thiol / hydroxyl / carboxyl / sulfonic acid groups; The total solute concentration of modified solution A is 1 to 5 g / L; The solvent of the modified liquid A is a mixture of deionized water and an organic solvent; The boiling point of the organic solvent is bp≤150℃ and the toxicity is LD50≥2900 mg / kg; The volume ratio of deionized water to organic solvent in modified liquid A is 1:(0.25~4).
6. The method for preparing the ultra-thin copper foil for packaging substrate according to claim 1, It is characterized in that The thickness of the conductive layer (3) in step 3 is 800 to 2500 Å; The material of the conductive layer (3) is an iron-based alloy layer, a cobalt-based alloy layer, a titanium-based alloy or conductive carbon.
7. The method for preparing the ultra-thin copper foil for packaging substrate according to claim 1, It is characterized in that The soaking temperature in step 4 is 20-30°C, and the soaking time is 30-70s.
8. The method for preparing the ultra-thin copper foil for packaging substrate according to claim 1, It is characterized in that The solute of the modified solution B in step 4 is one or two of triazole / thiazole / thiadiazole / imidazole small molecule (Mw≤200 g / mol) compounds; The total solute concentration of modified solution B is 1 to 5 g / L; The solvent of the modified liquid B is a mixture of deionized water and an organic solvent; The volume ratio of water to organic solvent in the solvent of modified liquid B is 1:(0.05~2); The boiling point of organic solvents is bp≤150℃ and the toxicity is LD50≥2900 mg / kg.
9. The method for preparing the ultra-thin copper foil for packaging substrate according to claim 1, It is characterized in that The copper salt concentration in the copper electroplating solution in step 5 is 100 to 300 g / L; Sulfuric acid concentration is 50-120 g / L; The Cl / Br ion concentration is 20-300 mg / L; The concentration of sodium polydisulfide dipropane sulfonate is 0.2~1.2 g / L; Hydroxymethylcellulose concentration ≤ 100 mg / L; Gelatin concentration ≤80 mg / L; Polyethyleneimine concentration ≤ 1000 mg / L; The molecular weight of polyethyleneimine is Mw≤10 kDa.
10. A method for preparing a copper clad laminate, It is characterized in that An ultra-thin copper foil (1) is prepared by the method for preparing an ultra-thin copper foil for a packaging carrier as claimed in any one of claims 1 to 9, and the ultra-thin copper foil (1) is pressed onto a prepreg (5) by means of heat pressing; During pressing, the temperature is 30~320℃; Time is 2~6 hours; Pressure is 2~4.5 MPa; The thickness of the prepreg (5) is 1 to 30 mm; The prepreg (5) is one of epoxy resin, phenolic resin, polyester and polytetrafluoroethylene; During lamination, one side of a carrier substrate (4) having an ultra-thin copper foil (1) is adhered to a prepreg (5), and then lamination is performed by heat pressing. After lamination, the carrier substrate (4), the conductive layer (3) and the organic coating (2) are peeled off to form a copper clad laminate.
